A relational database for bibliometric analysis - Nicolai Mallig (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2010)
In this article a relational database schema for a bibliometric database is developed. After the introduction explaining the motivation to use relational databases in bibliome-trics, an overview of the related literature is given. A review of typical bibliometric ques-tions serves as an informal requirement analysis. The database schema is developed as an entity-relationship diagram using the structural information typically found in scientific articles. Several SQL queries for the tasks presented in the requirement analysis show the usefulness of the developed database schema.
urn:nbn:de:0011-n-1622801
Keywords: 330; bibliometrics; relational database; SQL